Public Awareness in the Management of Death Certificates for Population Administration Order at the Population and Civil Registration Office of Sidoarjo Regency: Kesadaran Masyarakat Dalam Pengurusan Akta Kematian Untuk Ketertiban Administrasi Kependudukan di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Sidoarjo - Islami, Susila Nur; Rodiyah, Isnaini (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to describe public awareness in the management of death certificates in the population administration order at the Population and Civil Registry Office of Sidoarjo Regency. The method used in this research is descriptive qualitative method. Data collection techniques obtained are interviews, field observations and documentation. The results showed that the level of public awareness in the management of death certificates was still low. The public still does not have good knowledge about the management of death certificates. The low interest of the public in managing death certificates is due to the lack of public understanding of the function of the death certificate itself. Factors that affect public awareness: First, personal interests, some people who take care of death certificates are people who have personal interests. Second, the lack of public understanding of death certificates makes public awareness in the management of death certificates still low. Third, the lack of socialization carried out by both relevant agencies and village officials is needed to increase public understanding and legal awareness of the community.